Neutrophil decline rate following autologous transplant for lymphoma is a predictor of patients' outcome. Issue 5 (16th April 2022) - Lebel, Eyal; Vainstein, Vladimir; Ashkenazi, Maayan; Zimran, Eran; Stepensky, Polina; Grisariu, Sigal; Avni, Batia
Abstract: Neutropenia postchemotherapy is associated with favorable outcomes, which was attributed to optimal dosing. However, little is known about the neutrophil decline rate as a predictor of cancer outcomes, which may reflect a dynamic marker of chemosensitivity. We assessed the association between the neutrophil decline rate and disease outcomes in a known cohort of 212 lymphoma patients, treated with thiotepa, etoposide, cyclophosphamide, cytarabine, and melphalan (TECAM) conditioning followed by autologous transplant in our center between 2000 and 2013. Slower neutrophil decline rate was correlated with worse overall survival, mediated not by shorter time to progression (TTP), but rather by worse survival post-progression, possibly pointing to chemosensitivity at each line of therapy as the responsible mechanism. The effect was seen across histologies and was independent of stronger predictors of outcome like performance status (PS) and response before transplant. Prospective research is needed to confirm our results and expand their validity to other clinical scenarios.